Manfaat dan Tantangan Penggabungan Pengukuran Objektif dan Subjektif dalam Penelitian Arsitektur - Ferdy Sabono; Iwan Sudradjat; Indah Widiastuti (Universitas Sebelas Maret Surakarta, 2023)
Inaccuracy in choosing and using the type of measurement will result in biased research findings. Measurements commonly used in architectural research are objective, subjective, or objective-subjective (mixed) measurements. This article will discuss mixed measures (objective and subjective) in architectural research. Researchers can analyze field data using a quantitative approach, while subjective measurement data are analyzed using a qualitative approach. The results of the interpretation of the two types of measures can show convergence or divergence. This article aims to reveal the benefits and challenges of combining objective and subjective measurements in architectural research, based on systematic literature reviews in scientific journals, which have successfully used objective-subjective measurements and outlines the various benefits and challenges. This study shows that using objective-subjective measures in architectural research can be beneficial if done in an appropriate context.